Building blocks of a flip-chip integrated superconducting quantum processor - Kosen, Sandoko; Li, Hang-Xi; Rommel, Marcus; Shiri, Daryoush; Warren, Christopher; Gronberg, Leif; Salonen, Jaakko; Abad, Tahereh; Biznarova, Janka; Caputo, Marco; Chen, Liangyu; Grigoras, Kestutis; et al. (Quantum Science and Technology, 2022)
We have integrated single and coupled superconducting transmon qubits into flip-chip modules. Each module consists of two chips - one quantum chip and one control chip - that are bump-bonded together. We demonstrate time-averaged coherence times exceeding 90 μs, single-qubit gate fidelities exceeding 99.9%, and two-qubit gate fidelities above 98.6%. We also present device design methods and discuss the sensitivity of device parameters to variation in interchip spacing. Notably, the additional flip-chip fabrication steps do not degrade the qubit performance compared to our baseline state-of-the-art in single-chip, planar circuits. This integration technique can be extended to the realisation of quantum processors accommodating hundreds of qubits in one module as it offers adequate input/output wiring access to all qubits and couplers.
Created from Fastlane, Scopus look-up
Keywords: coherence times; design and simulation; flip-chip integration; gate fidelities; superconducting qubit; transmon